Inhaled corticosteroid treatment and pneumonia in patients with chronic obstructive pulmonary disease – nationwide development from 1998 to 2018 - Allan Klitgaard; Rikke Ibsen; Jesper Lykkegaard; Ole Hilberg; Anders Løkke (European Clinical Respiratory Journal)
Background A decreasing use of inhaled corticosteroids (ICS) in patients with a hospital-registered diagnosis of chronic obstructive pulmonary disease (COPD) has recently been documented in Denmark. ICS treatment is not recommended in patients with high pneumonia risk, and we aimed to assess the development of ICS treatment in relation to pneumonia occurrence.Methods Annual nationwide register-based cross-sectional studies from 1998 to 2018 including all patients ≥40 years of age with a hospital-registered ICD-10 diagnosis of COPD on the 31st of December each year. We calculated the annual proportion of patients with at least one outpatient pneumonia (redeemed prescription of relevant antibiotics) or pneumonia hospitalization (hospitalization or ER visit), and stratified by ICS dose (No ICS, low dose, medium dose, or high dose).Results The study population increased from 35,656 patients in 1998 to 99,057 patients in 2018. The annual proportion of patients experiencing a pneumonia decreased from 69.4% to 55.2%. The proportion of patients with at least one outpatient pneumonia, but no hospitalization, decreased (59.2% to 46.2%). The overall proportion of patients with at least one pneumonia hospitalization remained unchanged (10.2% to 9.0%), but this proportion increased in patients in high dose ICS (9.9% to 14.6%). The overall proportion of patients in high dose treatment decreased (12.7% to 5.7%), but not in patients with pneumonia hospitalization (16.5% to 15.1).Conclusions Our study demonstrates a nationwide decrease from 1998 to 2018 in the proportion of patients who redeemed a prescription for antibiotics used mainly for respiratory tract infections, which may reflect a decrease in the number of outpatient pneumonias. This decrease was largely caused by an increase in the number of patients without pneumonia. No differences over time were seen regarding hospitalization-requiring pneumonia. High dose ICS treatment was unchanged in patients with hospitalization-requiring pneumonia.